Pengaruh Ukuran Perusahaan, Leverage, Dan Profitabilitas Terhadap Manajemen Laba: Studi Kasus Pada Perusahaan Industri Pariwisata Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - M Sendi Feby Andika; Nisrina Aulia Pradipta; Lia Uzliawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Earnings management practices due to the Covid-19 pandemic are a problem in this research. The purpose of this research is to examine the influence of company size, leverage and profitability on earnings management. Data obtained from financial reports of tourism industry companies listed on the IDX. The sample consisted of 15 tourism industry companies listed on the IDX throughout 2019-2021 based on a purposive sampling technique. The analysis used is panel data regression analysis. 1) Earnings management can be significantly influenced simultaneously by company size, leverage and profitability; (2) Company size has a significant effect on earnings management; (3) Leverage has a significant influence on earnings management; (4) Earnings management is not significantly influenced by profitability. Keywords: Earnings Management, Company Size, Leverage, Profitability, Tourism